- #1

- 10,877

- 422

## Homework Statement

I want to prove that if X is a normed space, the following statements are equivalent.

(a) Every Cauchy sequence in X is convergent.

(b) Every absolutely convergent series in X is convergent.

I'm having difficulties with the implication (b) ⇒ (a).

## Homework Equations

Only some standard definitions.

## The Attempt at a Solution

I have no problems with the implication (a) ⇒ (b). I'm including the proof only because it can perhaps provide some inspiration for the proof of the converse.

**(a) ⇒(b):**Let ##\sum_{k=1}^\infty x_k## be an arbitrary absolutely convergent series in X. For each ##n\in\mathbb Z^+##, define ##s_n=\sum_{k=1}^n x_k## and ##t_n=\sum_{k=1}^n \|x_k\|##. The desired result follows from

$$\|s_n-s_m\|=\left\|\sum_{k=m+1}^n x_k\right\| \leq\sum_{k=m+1}^n\|x_k\| =|t_n-t_m|.$$ The argument is simple: ##(t_n)## is convergent and therefore Cauchy. This and the inequality above together imply that ##(s_n)## is Cauchy. Now (a) implies that ##(s_n)## is convergent.

Here's the part I'm struggling with:

**(b) ⇒ (a):**Let ##(s_n)## be an arbitrary Cauchy sequence in X. I'm using the notation ##s_n## rather than ##x_n## because I'm going to define a sequence ##(x_n)## such that ##(s_n)## is its sequence of partial sums. We define ##x_1=s_1## and for each ##n\geq 2##, ##x_n=s_n-s_{n-1}##. We have

$$\sum_{k=1}^n x_k =(s_n-s_{n-1})+(s_{n-1}-s_{n-2})+\cdots+(s_2-s_1)+s_1 =s_n.$$ If we can show that ##\sum_{k=1}^\infty x_k## is absolutely convergent, we're done. Unfortunately that doesn't look possible. I think we have to continue something like this: For each ##k\in\mathbb Z^+##, let ##n_k## be a positive integer such that

$$i,j\geq n_k\ \Rightarrow\ \|s_i-s_j\|<2^{-k}.$$ Let ##k\in\mathbb Z^+## be arbitrary. Define ##m_k=n_k+1##. We have

$$\|x_{m_k}\|=\|s_{m_k}-s_{m_k-1}\|=\|s_{n_k+1}-s_{n_k}\|<2^{-k}.$$ Does this help at all? It tells us that ##\sum_{k=1}^\infty x_{m_k}## is absolutely convergent, and therefore convergent. But how does knowing that ##\sum_{k=1}^\infty x_{m_k}## is convergent help us? It means that the sequence ##\big(\sum_{k=1}^p x_{m_k}\big)_{p=1}^\infty## is convergent, but this isn't a subsequence of ##(s_n)##. ##(s_{m_p})_{p=1}^\infty## is a subsequence of ##(s_n)##, but I don't see why it would be convergent.